A study on antimicrobial and anticancer properties of Cissus quadrangulris using lung cancer cell line - Sholapuri Payani; Matcha Bhaskar; Gandham Sandeep Kumar; Jangampalli Adi Pradeepkiran (Cancer Treatment and Research Communications, 2023)
Cissus quadrangularis plant from Vitaceae family, native in India. Many parts of this plant have medicinal values but most precious is stem of this plant. In past years number of studies reported their activities and secondary metabolites in Cissus quadrangularis plant and their pharmacological activities and uses in traditional medicine system. It is reported to possess excellent medicinal properties and potent fracture healing properties, antimicrobial, antiulcer, antioxidative, cholinergic activity and beneficial effect on cardiovascular diseases, possesses antiulcer and cytoprotective property in indomethacin-induced gastric mucosal injury. The aim of this study was to determine the qualitative phytochemical analysis, antimicrobial activity, cell viability and in vitro anticancer activity of a potential of Cissus quadrangularis stem extract against A549 human lung cancer cell line. The disc diffusion method was employed to determine the antimicrobial activity of Cissus quadrangularis stem extract and showed potential antibacterial and antifungal activity against various microorganisms. Results have shown that Stem methanolic extract induced a significant decrease of tumour cell viability. The cell viability assay clearly showed that the cells treated with Cissus quadrangularis methanolic extract has significantly reduced the lung cancer cell viability in a dose dependant manner. The stem methanolic extract was tested for the in vitro antiproliferative potential on A549 human lung cancer cell line using different concentrations, namely 1000, 62.5 and 7.8 µg/ml. We observed the IC50 dose at 65.2 μg/ml concentration. In cell culture A549 cells treated with Cissus quadrangularis stem methanolic extract in 24 h the cells growth is controlled.